Multivalent thioglycopeptoids via photoclick chemistry: potent affinities towards LecA and BC2L-A lectins1. Issue 61 (7th August 2015) - Caumes, C.; Gillon, E.; Legeret, B.; Taillefumier, C.; Imberty, A.; Faure, S.
<x xml:space="preserve">Abstract</x> The straightforward access to peptoid-based multivalent thioglycoclusters displaying 1-thio-β-d-galactose or 1-thio-α/β-d-mannose and their evaluation towards two bacterial lectins are described.